2013
DOI: 10.1016/j.celrep.2013.02.025
|View full text |Cite|
|
Sign up to set email alerts
|

Substrate-Activated Conformational Switch on Chaperones Encodes a Targeting Signal in Type III Secretion

Abstract: SUMMARY Targeting of type III secretion proteins at the injectisome is an important process in bacterial virulence. Nevertheless, how the injectisome specifically recognizes TTS substrates among all bacterial proteins is unknown. A TTS peripheral membrane ATPase protein located at the base of the injectisome has been implicated in the targeting process. We have investigated the targeting of the EspA filament protein and its cognate chaperone CesAB to the EscN ATPase of the enteropathogenic E. coli (EPEC). We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 48 publications
0
52
1
1
Order By: Relevance
“…Indeed, InvE, a Salmonella homolog of SepL and YopN, does not interact with either the translocators or their chaperone individually but can form a complex when all these proteins are present (53). It has recently been shown by using nuclear magnetic resonance (NMR) spectroscopy that the interaction between EscN and CesAB occurs only after binding of CesAB to EspA, which results in conformational changes in CesAB exposing a targeting signal to EscN (54). Concluding remarks.…”
Section: Wclmentioning
confidence: 99%
“…Indeed, InvE, a Salmonella homolog of SepL and YopN, does not interact with either the translocators or their chaperone individually but can form a complex when all these proteins are present (53). It has recently been shown by using nuclear magnetic resonance (NMR) spectroscopy that the interaction between EscN and CesAB occurs only after binding of CesAB to EspA, which results in conformational changes in CesAB exposing a targeting signal to EscN (54). Concluding remarks.…”
Section: Wclmentioning
confidence: 99%
“…Recent structural data showed that some effector/chaperone complexes can form hexamers, which would fit the hexameric ATPase structure [217]. Interestingly, it was shown that targeting to the ATPase and secretion are largely independent events: while chaperone binding, rather than presence of the secretion signal, was required for association of a substrate with the ATPase, this was insufficient for secretion of the substrate [218].…”
Section: Type III Secretion Export Is a Multi-step Process With Many mentioning
confidence: 99%
“…Because the internal diameter of the needle is on the order of 25 Å, it is believed that effectors must travel in a semi-unfolded state (2, 3) due to energy provided by an ATPase located at the base of the system (4 -6). Introduction of point mutations into key proteins of the T3SS have shown to be highly deleterious for the cytotoxicity potential of certain pathogens (7)(8)(9)(10)(11), and T3SS-deficient strains display attenuated infectivity in animal models (12)(13)(14), indicating that an understanding of T3SS formation and regulation mechanisms could lead to the development of strategies for infection control.…”
mentioning
confidence: 99%